Pengaruh Latihan Drill Passing Terhadap Akurasi Passing Pada Futsal SMPN 32 Kota Bekasi - Utomo, Ridho Tri; Prawira, Asrori Yudha; Candra, Juli; Denatara, Eskar Tri; 'Ala, Faridatul (JURNAL ILMIAH NUSANTARA, 2025)
Futsal is a sport that requires quick thinking and mastery of basic technical skills such as passing, control, dribbling, and shooting, along with good teamwork in a limited space. At SMPN 32 Kota Bekasi, most students have not yet mastered proper passing techniques, such as using the inside of the foot to produce accurate and on-target passes. Many students still use the outside of the foot for passing and fail to pay attention to body position when passing the ball, resulting in passes often missing their target. The purpose of this study is to determine the effect of passing drill training on passing accuracy in futsal at SMPN 32 Kota Bekasi. The study was conducted using an experimental method with a pre-experimental design to examine the effect of drill training methods on improving basic futsal passing skills. The results of this study indicate that passing drill training has a significant impact on improving the passing accuracy of futsal students in the extracurricular program at SMPN 32 Kota Bekasi.